Panax notoginseng preparation plus aspirin versus aspirin alone on platelet aggregation and coagulation in patients with coronary heart disease or ischemic stroke: A meta-analysis of randomized controlled trials - Dai, Lulu; Zhang, Ying; Jiang, Yuerong; Chen, Keji (Frontiers in Pharmacology, 2022)
Purpose: We aimed to evaluate the effects of Panax notoginseng preparations (PNP) containing Panax Notoginseng Saponins (PNS) or Panaxatriol Saponin (PTS) on platelet aggregation and coagulation in the adjuvant treatment of coronary heart disease (CHD) and ischemic stroke (IS). Methods: Randomized controlled trials (RCTs) comparing the combination of PNP and aspirin (ASA) versus ASA alone for CHD or IS were searched in eight databases. Subgroup analysis was performed according to saponin category. When statistical heterogeneity was significant, sensitivity analysis was performed using the leave-one-out approach. Funnel plot, Egger’ test, and Begg’ test was adopted to detect publication bias. Results: Twenty RCTs involving 2216 patients were analyzed. Compared with ASA alone, PNP plus ASA had a stronger inhibitory effect on in PAgR [PNS, WMD = -6.10 (-7.25, -4.95), P < 0.00001; PTS, WMD = -3.53 (-4.68, -2.38), P < 0.00001]; PNS plus ASA better reduced FIB [WMD = -0.43 (-0.49, -0.36)] and DD [WMD = -0.59 (-0.67, -0.51), P < 0.00001], while PLT (P = 0.07) and PT (P = 0.34) were not significantly different; PTS plus ASA better prolonged PT [WMD = 1.90 (1.47, 2.32), P < 0.00001] and PT-INR [WMD = 0.22 (0.11, 0.32), P < 0.0001], whereas no significant difference in DD (P = 0.1) and bleeding-related events (positive fecal occult blood, P = 0.96; upper gastrointestinal bleeding, P = 0.67; subcutaneous hemorrhage, P = 0.51; bulbar conjunctival hemorrhage, P = 0.51; hematuria, P = 0.58). There was no significant difference between PNP plus ASA and ASA alone in terms of gastrointestinal side effect (PNS, P = 0.65; PTS, P = 0.56) and urticaria (PNS, P = 0.57; PTS, P = 0.55). Conclusions: PNP combined with ASA might produce stronger antiplatelet aggregation and anticoagulation effects without increasing bleeding risk, gastrointestinal side effects, and urticaria compared with ASA alone. Keywords: Panax notoginseng preparation, aspirin, Panax Notoginseng Saponins, Panaxatriol Saponin, platelet aggregation, coagulation, meta-analysis.